2018
DOI: 10.1186/s12905-018-0639-4
|View full text |Cite
|
Sign up to set email alerts
|

“I don’t need a flat tummy; I just want to run fast” – self-understanding and bodily identity of women in competitive and recreational sports

Abstract: BackgroundWomen who exercise intensively, whether competitive or recreational, devote a lot of time and energy into exercise, which requires high levels of ambition and motivation. The aim of the study is to investigate the self-understanding and bodily identity of different (competitive vs recreational) forms of exercise, and to investigate the role of important others (parents, siblings and social relations) for this self-understanding.MethodsA qualitative study using semi-structured interviews. An interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Frequent injuries and difficulty recoveries are further barriers to remaining in competitive sport (Isorna et al, 2019). Participants report how the injuries they have suffered often take an emotional toll on them due to their deep attachment to sport, as previously identified by Roessler and Muller (2018). The intense and continuous competitive pressure athletes are subjected to over time is another factor that causes them to retire from competitive sport, as previous research has also shown (Dwyer et al, 2006;Galatti et al, 2019;Isorna et al, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…Frequent injuries and difficulty recoveries are further barriers to remaining in competitive sport (Isorna et al, 2019). Participants report how the injuries they have suffered often take an emotional toll on them due to their deep attachment to sport, as previously identified by Roessler and Muller (2018). The intense and continuous competitive pressure athletes are subjected to over time is another factor that causes them to retire from competitive sport, as previous research has also shown (Dwyer et al, 2006;Galatti et al, 2019;Isorna et al, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…Meanwhile, the external environmental factors affecting women’s fitness demands are mainly reflected in their social and family environment. Many studies have shown that social and family environment affect people’s motivation, especially the motivation and behavior of married women [ 6 , 16 , 26 ]. Among these, family environment is the main external factor affecting women’s fitness preference or time and opportunity for fitness participation.…”
Section: Results and Analysismentioning
confidence: 99%
“…For example, women aged 26–35 participate in sports for leisure and in order to accompany their family [ 21 , 22 , 23 , 24 , 25 ]. The top three reasons why women aged 36–45 participate in sports are to strengthen their health [ 26 , 27 ], relieve stress, and accompany their families [ 28 , 29 , 30 , 31 ]. Women aged 46–50 mainly participate in sports to strengthen their health, to accompany their families, and to prevent diseases [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…La planificación y la organización se hacen indispensables para las mujeres deportistas, que tienen que compaginar un gran número de actividades y roles (estudios, trabajo o responsabilidades familiares) con la práctica deportiva (Gallego 2008). En este sentido, para muchas parece que el deporte les ha enseñado el valioso significado de la organización (Roessler y Muller 2018).…”
Section: Aurora: Yo Por Ejemplo En éPocas De Exámenes Que Te Agobias Mucho Y Dices Si No Entrenara Hoy Que Tengo Mucho Que Estudiar Y Talunclassified